2019
DOI: 10.3390/w11091802
|View full text |Cite
|
Sign up to set email alerts
|

The-Proof-of-Concept of Biochar Floating Cover Influence on Water pH

Abstract: Studies have shown that biochar has the potential to remove organic and inorganic contaminants from wastewater. pH is known to have a crucial role in the transformation of pollutants. In this research, we explore the feasibility of using biochars properties to control the pH near the water-air interface, so the gaseous emissions from water (or wastewater) could be mitigated. This study aimed to test the effects of a thin layer biochar addition on the spatial and temporal variation of water pH. Two types of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 25 publications
0
29
2
Order By: Relevance
“…Ayiania et al studied that the mechanism of H2S sorption is driven by the size of biochar pores [49]. However, our experiments showed that HAP biochar with pH=9.2 and larger pores [34] performed less H2S reduction in comparison with RO over all three trials. It should be mentioned that FTIR spectra (Figure 7) showed that RO had higher peaks in OH and COOstretching.…”
Section: Effect Of Biochar Treatment On Ammonia and Hydrogen Sulfidementioning
confidence: 52%
See 4 more Smart Citations
“…Ayiania et al studied that the mechanism of H2S sorption is driven by the size of biochar pores [49]. However, our experiments showed that HAP biochar with pH=9.2 and larger pores [34] performed less H2S reduction in comparison with RO over all three trials. It should be mentioned that FTIR spectra (Figure 7) showed that RO had higher peaks in OH and COOstretching.…”
Section: Effect Of Biochar Treatment On Ammonia and Hydrogen Sulfidementioning
confidence: 52%
“…Fixed C content was estimated by subtracting percentages of moisture, volatile matter, and ash content from the sample [41]. Results of the elemental analyses, moisture/fixed C, volatile matter, and pH are summarized elsewhere [34]. In addition, a solid addition method was used to analyze the zero point charge (ZPC) of biochars.…”
Section: Biochar Propertiesmentioning
confidence: 99%
See 3 more Smart Citations